Strain Driven Electrical Bandgap Tuning of Atomically Thin WSe2 - Md Akibul Islam; Eric Nicholson; Nima Barri; Momoko Onodera; Danny Starkov; Peter Serles; Shuo He; Boran Kumral; Ali Zavabeti; Haleh Shahsa; Teng Cui; Guorui Wang; et al. (Advanced Electronic Materials)
Abstract Tuning electrical properties of 2D materials through mechanical strain has predominantly focused on n‐type 2D materials like MoS2 and WS2, while p‐type 2D materials such as WSe2 remain relatively unexplored. Here, the impact of controlled mechanical strain on the electron transport characteristics of both mono and bi‐layer WSe2 is studied. Through coupling atomic force microscopy (AFM) nanoindentation techniques and conductive AFM, the ability to finely tune the electronic band structure of WSe2 is demonstrated. The research offers valuable mechanistic insights into understanding how WSe2's electronic properties respond to mechanical strain, a critical prerequisite for the development of flexible photoelectronic devices. It is also observed that under high pressure, the AFM tip/monolayer WSe2/metal substrate junction transitions from Schottky to Ohmic contact, attributed to significant charge injection from the substrate to the WSe2. These findings are significant for designing efficient metal/semiconductor contact in thin and flexible PMOS (p‐type Metal–Oxide–Semiconductor) devices.